Three pigs, One wolf, and seven magic shapes - Maccarone , Grace (New York : Scholastic Inc, 1997)
Tells the story of three pigs who acquire some magic shapes, which they use for various purposes, some smart and some not so smart. Includes a section with related activities.
"Cartwheel books." "Geometry"-- Cover 1 & 2
Keywords: Shape -- Fiction; Tangrams -- Fiction